A review on recent progress and selection of cobalt-based cathode materials for low temperature-solid oxide fuel cells. (March 2022) - Vinoth Kumar, R.; Khandale, A.P.
Abstract: Solid oxide fuel cells (SOFCs) are versatile, and highly efficient power source perceived as future of the energy. Lower operating temperatures in the range of 400–600 °C can considerably increase applications for this technology and can facilitate use of a wider variety of materials in SOFC with greater reliability. Sluggish oxygen reduction kinetics and long-term chemical instability of cathode restricts practical use of low temperature (LT)-SOFC. This review article focusses on the potential cobalt-based cathodes showing promising electrocatalytic activity at low temperatures (≤600 °C). Combine use of novel elements in the architecture of SOFC and incorporating advances in new materials can enable operation of LT-SOFC with higher efficiency. Based on the review conducted, it is found that anode supported SOFC based on SrCo0·8 Nb0·1 Ta0·1 O3− δ cathode and GDC electrolyte exhibits excellent electrochemical performance (1200 mW cm −2 ) below 500 °C, so far. Ni-GDC anode supported cell based on thin film GDC electrolyte and Ba0·5 Sr0·5 Co0·8 Fe0·2 O3- δ cathode shows a power output of 454 mW cm −2 at 500 °C, which is higher than La0·6 Sr0·4 Co0·2 Fe0·8 O3 and Sm0.5 Sr0·5 CoO3- δ -based cathodes however still lower than SrCo0·8 Nb0·1 Ta0·1 O3− δ at same operating conditions and suffers CO2 poisoning. In contrast, Cr and Si poisoning in case of double perovskites restrict their use below 600 °C. Further, cathode performance and its stability can be enhanced by the decoration of metal nanoparticles or thin-films on cathodes. Metal exsolved perovskite cathode shows better performance and long-term stability compare to wet impregnated cathode, as the nanoparticles are firmly anchored to the oxide surface. Thus, novel strategies are highly desired for the development of cathode to achieve highly efficient LT-SOFC as sensible power source resulting into the stability of our environment, energy supply, and economy. Graphical abstract: Image 1 Highlights: Addressing cathode polarization is essential to reduce temperature of SOFC to ≤600 °C. Cobalt-based cathodes exhibit high oxygen flux and electrocatalytic activity for ORR. Highly porous and continuous nano-structure facilitates excellent gas transport property.